Preserving Woodenware in Beekeeping Operations - James D. Ellis; William H. Kern; Catherine M. Zettel Nalen (EDIS, 2012)
The predominant material used to construct honey bee colonies in the U.S. is wood. Though honey bee hive components are simple in design, they are subjected to many extreme management techniques that cause wear and tear, ultimately shortening the life of the equipment. This article discusses how to protect colony woodenware, particularly the pieces that are exposed to the elements. These include the bottom board, hive body/supers, and lids. This revised 4-page fact sheet was written by J. D. Ellis, W. H. Kern, and C. M. Zettel Nalen, and published by the UF Department of Entomology and Nematology, June 2012.